Consequences of proline‐to‐alanine substitutions for the stability and refolding of onconase. (12th July 2013) - Hacke, Mandy; Gruber, Tobias; Schulenburg, Cindy; Balbach, Jochen; Arnold, Ulrich
Abstract : Peptidyl‐prolyl isomerization reactions can make for rate‐limiting steps in protein folding due to their high activation energy. Onconase, an unusually stable ribonuclease A homologue from the Northern leopard frog, contains four trans proline residues in its native state. During the refolding from its guanidine hydrochloride unfolded state, which includes the formation of a folding intermediate, the slowest of the three phases has earlier been attributed to a cis ‐to‐ trans peptidyl‐prolyl isomerization reaction. We thus substituted all four proline residues individually by alanine and investigated the effect of the amino acid substitutions on the folding and stability of the onconase variants. All onconase variants proved to adopt a tertiary structure comparable with that of the wild‐type protein. Although the slow phase was not eliminated for any of the variants, the P43A substitution resulted in an increase in the rate constant of the fast folding phase, i.e. a faster formation of the folding intermediate. This variant also exhibits a significant increase in thermodynamic stability. As residue 43 belongs to those residues that are protected from hydrogen exchange with the solvent in the folding intermediate, the increase in the rate constant and stability of the P43A variant emphasizes the importance of the intermediate for the folding of onconase. Enzymes: Onconase (EC 3.1.27.5) Abstract : Onconase contains four trans prolines. Its refolding, which includes a folding intermediate, comprises a slow phase possibly originating from a cis ‐to‐ trans peptidyl‐prolyl isomerization. We substituted all four prolines individually by alanines. The slow phase was not eliminated for any of the variants, but the P43A substitution resulted in a faster formation of the intermediate and a significant increase in thermodynamic stability.